Metformin pharmacokinetics in nondiabetic pregnant women with polycystic ovary syndrome - de Oliveira Baraldi, Cláudia; Lanchote, Vera Lucia; de Jesus Antunes, Natalícia; de Jesus Ponte Carvalho, Teresa Maria; Dantes Moisés, Elaine Christine; Duarte, Geraldo; Cavalli, Ricardo Carvalho (European journal of clinical pharmacology, 2011)
Background The use of metformin throughout gestation by pregnant women with polycystic ovary syndrome (PCOS) significantly reduces the number of first trimester spontaneous abortions and the rate of occurrence of gestational diabetes. Objective The objective of this study was to investigate the pharmacokinetics and the placental transfer of metformin in pregnant women with PCOS. Patients and methods Eight pregnant women with PCOS taking 850 mg metformin every 12 h during the third trimester of pregnancy were evaluated. Maternal blood samples were collected at steady state during the dose interval (0–12 h). Maternal and umbilical cord blood samples were also obtained at delivery. Metformin plasma concentrations were analyzed by high-performance liquid chromatography, and pharmacokinetic parameters were determined using a non-compartmental model. Data are reported as median and minimum and maximum values. Results Metformin pharmacokinetic parameters were: t ½ , 3.8 (2.8–5.4) h; t max , 2.0 (0.5–3.0) h; C max , 1.4 (0.5–2.1) mg/L; C mean , 0.5 (0.2–0.9) mg/L; AUC 0–12 , 6.4 (1.1–9.2) mg h/L; Cl/f, 105 (60–274) L/h; Vd/f, 551 (385–1173) L; median fluctuation, 89 (79–95)%. Umbilical/maternal metformin plasma concentration ratios were 0.7 (0.4–1.3). Conclusion Metformin oral clearance (Cl/f) had increased in our patients relative to nonpregnant healthy volunteers or diabetic patients. Therefore, lower plasma metformin concentrations were observed for nondiabetic pregnant women with PCOS. Future studies should be conducted to demonstrate the therapeutic efficacy of metformin during pregnancy. Caution is warranted as umbilical/maternal metformin plasma concentrations ratios of around 0.7 require metformin dosage adjustment.